2002
DOI: 10.1042/bj20020127
|View full text |Cite
|
Sign up to set email alerts
|

Mu-class glutathione transferase from Xenopus laevis: molecular cloning, expression and site-directed mutagenesis

Abstract: A cDNA encoding a Mu-class glutathione transferase (XlGSTM1-1) has been isolated from a Xenopus laevis liver library, and its nucleotide sequence has been determined. XlGSTM1-1 is composed of 219 amino acid residues with a calculated molecular mass of 25359 Da. Unlike many mammalian Mu-class GSTs, XlGSTM1-1 has a narrow spectrum of substrate specificity and it is also less effective in conjugating 1-chloro-2,4-dinitrobenzene. A notable structural feature of XlGSTM1-1 is the presence of the Cys-139 residue in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Unlike mammalian GSTs, little is known about this family of proteins in amphibians. A few studies identified and characterized the different classes of GSTs present in X. laevis and mu, alpha, sigma, and pi classes have been found De Luca et al, 2002. However, the responses and regulation of these different classes of GSTs with respect to environmental stress in X. laevis has not previously been examined.…”
Section: Discussionmentioning
confidence: 96%
“…Unlike mammalian GSTs, little is known about this family of proteins in amphibians. A few studies identified and characterized the different classes of GSTs present in X. laevis and mu, alpha, sigma, and pi classes have been found De Luca et al, 2002. However, the responses and regulation of these different classes of GSTs with respect to environmental stress in X. laevis has not previously been examined.…”
Section: Discussionmentioning
confidence: 96%
“…For each sample, we used 100 units of Moloney murine leukaemia virus reverse transcriptase and gene-specific reverse primer, according the manufacturer's instructions. The reaction was carried out in 50 mM Tris/HCl (pH 8.3), 75 mM KCl, 3 mM MgCl 2 , 5 mM dithiothreitol, 500 µM dNTP mix and 10 units of placental RNase inhibitor at 37 • C for 50 min, followed by 10 min at 90 • C. The following primers were used: Pirev (5 -TCACTTTTTGTGTTTGGGGG-3 ) for XlGSTP1-1; and Murev (5 -TTATTTTTTGTTGCCCCAGG-3 ) for XlGSTM1-1 [15].…”
Section: Rt-pcrmentioning
confidence: 99%
“…RT-PCR was performed to investigate the presence of the XlGSTP1 transcript during embryo development as well as in different adult tissues. XlGSTM1-1 [15] was used as a positive control to evaluate the sensitivity of the method (results not shown). Figure 3 shows that a 420 bp product corresponding to XlGSTP1-1 was present in embryos, but not in the unfertilized eggs, liver, lung, heart, kidney and ovary.…”
Section: Molecular Cloning Heterologous Expression and Tissue Distrimentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike mammalian GSTs, little is known about this family of proteins in amphibians. A few studies identified and characterized the different classes of GSTs present in X. laevis and mu, alpha, sigma, and pi classes have been found De Luca et al, 2002;De Luca et al, 2003).…”
Section: Discussionmentioning
confidence: 99%